Marxism and Deconstruction A Critical Articulation - Ryan, Michael (Johns Hopkins University Press, 2019)
Originally published in 1982. Aside from Jacques Derrida's own references to the "possible articulation" between deconstruction and Marxism, the relationship between the two has remained largely unexplored. In Marxism and Deconstruction, Michael Ryan examines that multifaceted relationship but not through a mere comparison of two distinct and inviolable entities. Instead, he looks at both with an eye to identifying their common elements and reweaving them into a new theory of political practice. To accomplish his task, Ryan undertakes a detailed comparison of deconstruction and Marxism, relating deconstruction to the dialectical tradition in philosophy and demonstrating how deconstruction can be used in the critique of ideology. He is a forceful critic of both the politics of deconstruction and the metaphysical aspect of Marxism (as seen from a deconstructionist perspective). Besides offering the first book-length study of Derrida in this context, Ryan makes the first methodic attempt by an American scholar to apply deconstruction to domains beyond literature. He proposes a deconstructive Marxism, one lacking the metaphysical underpinnings of conservative "scientific" Marxist theory and employing deconstructive analysis both for Marxist political criticism and to further current anti-metaphysical developments within Marxism. Marxism and Deconstruction is an innovative and controversial contribution to the fields of literary criticism, philosophy, and political science.